(untitled) (Microbes and Health, 2014)
An investigation was conducted for isolation, identification and determination of antibiotic sensitivity of Avibacterium paragallinarun, the causal agent of infectious coryza, from layer chickens. A total of 21 samples with characteristic symptoms of the disease were collected from a Hatchery of Gazipur. Tissue specimens obtained aseptically from swollen infra orbital sinus and tracheal swab were processed, of which, 3 were found positive while the rest 18 were negative. Isolation of bacteria was performed by first putting the specimen in Nicotinamide adenine dinucleotide (NAD) enriched phosphate buffer broth, anaerobically incubated for 24 hours followed by culturing loopful of broth on Blood agar (BA) and Chocolate agar (CA) plates enriched with NAD and streaked with feeder organism of Staphylococcus. aureus. On 24 hours of anaerobic incubation (candle jar method), dew drop satellite colonies of A. paragallinarum were visible on the culture plates. Cultural characteristics of bacteria as well as their staining, morphological, motility and biochemical properties such as sugar fermentation, MR and V-P tests, Indole production and catalase tests were recorded for identification. Further, antibiogram study revealed that the isolates were sensitive to Ciprofloxacin, Chloramphenicol and Gentamicin but resistant to Ampicillin, Amoxycillin, Oxytetracycline, Erythromycin and Sulphamethoxazole. DOI: http://dx.doi.org/10.3329/mh.v3i1.19769 Microbes and Health, June 2014. 3(1): 9-11